Comenio e l’infanzia - Cagnolati, Antonella (Studi sulla Formazione/Open Journal of Education, 2011)
The focus of the essay is an reinterpretation of Didactica Magna with particular attention to the dimension of childhood. The children are like “arbusculas Dei”: so the parents, but also those who preside over the political and ecclesiastical government of the whole community, must hasten to “plant, prune, irrigate”, because soon be seen in new generations clear progress towards of wisdom and piety. Important is the idea of Comenius to organize a nursery, thus bringing the education of children within a larger social project. The essay is an important contribution to the reinterpretation of pedagogical classics.